A Comparative Study of Ezra Pound’s Cantos on the domain of symbolism and W. B. Yeats’s occultism through A Vision - Güvel, Ayşe (Technium Social Sciences Journal, 2021)
The Cantos by Ezra Pound serves in a quintessential way to focus on the Modernist idea of literature. By defining the Modernist movement, it is emphasized in what aspects this movement penetrates the monumental poem, The Cantos. Alongside showing a sequence as to how modernism was formed and developed in time, the research provides a deeper understanding through Ezra Pound’s modernist perception and W. B. Yeats’s occultism over his work of art, A Vision. Pound’s epic poem, The Cantos and Yeats’s unique work, A Vision fulfill the need of a literary satiation in The Modernist period. By juxtaposing The Cantos and Yeats’s occultist perspective, the research probes the extent that the two works create a literary escapism, which attempts to balance the sanctity of human sanity. In the Modernist period, the period of picturing the frustration of the First World War, the interrelation of these works of art turns out a reflection of a literary recuperation from the cataclysm led by The Modernist world.